Thermal exergy optimisation for an irreversible cogeneration power plant. (28th June 2005) - Kaushik, S.C.; Chandra, H.; Khaliq, A.
The optimal design model, based on exergy analysis, of an irreversible cogeneration cycle has been presented using finite-time thermodynamics. The external irreversibility is due to the thermal resistance between the system and the heat reservoirs while the internal irreversibility is due to the non-isentropic compression and expansion process within the system. The internal irreversibility of the irreversible cogeneration cycle is characterised by a single parameter representing the ratio of relevant entropy differences. The presence of this irreversibility parameter shows that a cogeneration power plant with internal irreversibilities delivers less exergy output and has a lower efficiency than those of the reversible and endoreversible cycles. The model presented here is of more use when compared to those obtained by earlier researchers.